Maternal Atrioventricular Nodal Re-entrant Tachycardia During Pregnancy: Case Report - Podder, Priyanka; Saha, Joysree (Bangladesh Medical Journal, 2024)
During pregnancy, the physiological changes predispose a woman for the development of new-onset or recurrent arrhythmia. Atrioventricular nodal re-entrant tachycardia (AVNRT) is a common supraventricular tachycardia (SVT) in reproductive age of woman. Although often it is benign in nature but concerning. Electrical cardioversion is safe during pregnancy. Electrophysiological study (EPS) and Radiofrequency ablation (RFA) can be performed in selected patients. Hereby, we report a case of a woman in her second trimester of pregnancy presented with diagnosed case of AVNRT. She was monitored by multidisciplinary team. Electrocardiogram (ECG) and Echocardiogram reveals normal changes. EPS and RFA was done one year back at the time of diagnosis. At her 37 weeks of pregnancy, she developed scar tenderness. Emergency caesarean section was done in presence of cardiologist. Maternal and perinatal outcome were good. Bangladesh Med J. 2023 Jan; 52(1): 35-38